Greene’s dual-process moral psychology and the modularity of mind - Bammel, Moritz (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Joshua Greene has famously argued for two distinct processes of how humans make moral judgments. Despite a lively controversy around potential normative implications of this view, less attention has been paid to those philosophical assumptions that are fundamental to Greene’s dual-process theory itself. In this paper, I argue that Greene’s dual-process theory hinges on a modular account of cognition and the brain, and I critically discuss the plausibility of Greene’s view in light of increasing popularity of dynamical systems accounts in cognitive science. If we reject modularity and adopt a dynamical systems perspective instead, we can still hope to find relative differences in the functional specialization of dynamic brain networks within one interconnected system, but Greene’s original theory in terms of two asymmetrically independent processes will no longer be tenable. This imposes constraints on the kind of explanations that we can expect from an empirically informed ethics in that only non-exclusive dual-process theories would be compatible with a dynamical systems account. Ultimately, however, the controversy around the modularity of mind should not be misconceived as a purely empirical question, but rather as a matter of conflicting epistemic standards as to what qualifies as a good explanation in cognitive science.
Keywords: Dual-Process; Moral Judgment; Empirical Ethic; Modularity; Dynamical Systems Theory; Brain Network